Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Pemahaman Konsep Ipas Pada Siswa Mi Nurul Hidayah Nw Londar Tahun Ajaran 2025/2026 - M. Azmi Syukri Amin; Andri Afriani; Bq Indana Zulfa (Yayasan Azhar Amanaa Yogyakarta, 2026)
Low conceptual understanding of Natural and Social Sciences (IPAS) remains a persistent classroom problem in Madrasah Ibtidaiyah (MI), including at MI Nurul Hidayah NW Londar, where most third-grade students had not reached the Minimum Completeness Criteria (KKM) of 70. This study addresses that problem through the Discovery Learning model, which invites students to construct IPAS concepts themselves through observation, exploration, and inference rather than passively memorizing the teacher's explanations. The research employed Classroom Action Research (CAR) following the Kemmis and McTaggart model across two cycles, involving 21 third-grade students as research subjects, with data gathered through achievement tests, observation, and documentation. The results reveal a striking improvement: the class average rose from 62.38 in the pre-cycle to 73.57 in Cycle I and reached 84.52 in Cycle II, while classical completeness surged from only 23.81% to a full 100% by the end of Cycle II. Similar gains appeared in teacher and student engagement, both climbing into the Very Good category. These findings confirm that Discovery Learning is not merely an alternative technique but a proven strategy for turning a passive IPAS classroom into an active, meaningful, and student-centered learning space.